VAL34LEU POLYMORPHISM DETECTION BY REAL TIME PCR ASSAY USING FLUORESCENCE RESONANCE ENERGY TRANSFER ON ROTOR-GENE 6000 - Maryam NASER KAMJOO; Ali NAZEMI (Rojan GÜMÜŞ, 2016)
Factor XIII (FXIII) Val34Leu is the most important polymorphism of the A subunit in factor XIII gene. The aim of the present study was to develop an efficient method based on real time PCR with Fluorescence resonance energy transfer (FRET) detection and melting curve analysis for the detection of Val34Leu polymorphism.Specific primers were used to amplify the relevant fragment of the factor XIII-A gene and fluorescence resonance energy transfer hybridization probes were used for detection in a Rotor-Gene Q 5Plex HRM platform. Melting temperature (Tm) for the wild type was at 68.8, while Tm for homozygote mutant was at 63.8; heterozygote demonstrated both peaks.Our results showed that primers and probes propoesd in this study demonstrated a high specificity to identify wild type , heterozygous and homozygous mutantgenotypes. Due to the increasing molecular diagnosis in developing countries and the importance of identifying polymorphisms, this real time PCR assay is of great importance. An important advantage of this approach is the high sensitivity and specificity.